Basal Ganglia Volumes: MR-Derived Reference Ranges and Lateralization Indices for Children and Young Adults. Issue 5 (October 2014) - Wyciszkiewicz, Aleksandra; Pawlak, Mikolaj A.
Previous studies indicate rightward asymmetry of the caudate nucleus (CN) volume and leftward asymmetry of the putamen (PN) and globus pallidus (GP). This study aimed to estimate reference ranges for basal ganglia asymmetry in a large cohort of healthy individuals (n= 949), aged seven to 21 years. MRI images of 949 (320 female, mean age 12.6 +/− 3.3, range 7–21) healthy individuals were reviewed. Volumetric measurements of the basal ganglia were obtained using automated segmentation (FreeSurfer). We computed two lateralization indices: (L-R)/(L+R) (LI) and right/left ratio (RLR). Tolerance interval estimates were used to calculate reference ranges. Rightward asymmetry of the CN and leftward asymmetry of the PN and GP were confirmed. PN and GP volume decreased with age, but CN volume did not. The lateralization index decreased with age for PN, but not for CN and GP. RLR increased with age for PN and not for CN or GP. Females were associated with smaller volume, but not with either LI or RLR difference. Reference ranges obtained in this study provide useful resources for power analysis and a reference group for future studies using basal ganglia asymmetry indices.